Association between physical inactivity and socioeconomic status in adolescents - Carlos, Fabiangelo de Moura; Sousa, Paulo Henrique Alves de; Gonçalves Campos, Cezenário; Alves Lamounier, Joel; Costa Bila, Wendell; Caetano Romano, Márcia Christina (Revista Cuidarte, 2022)
Introduction: A sedentary lifestyle in adolescents contributes to the occurrence of different diseases, making it relevant to investigate associated factors. Objective: To analyze the association between sedentary lifestyle and socioeconomic status in adolescents from public schools. Materials and methods: Cross-sectional study, carried out with 347 adolescents enrolled in public high schools in the city of Divinópolis, Minas Gerais. Data collection took place in 2017. Sedentary lifestyle was assessed using the International Physical Activity Questionnaire and socioeconomic status using the criteria of the Brazilian Association of Research Companies. Descriptive and analytical statistics were performed using a multivariate logistic regression model. Results: 347 adolescents participated in the investigation. The mean age of the group was 16.4 ± 1.0 years. Individuals characterized as sedentary constituted 38.9% of the sample, of which 66.7% were female. Having a higher socioeconomic level decreases the probability of being sedentary (OR = 0,235; p = 0.021), just as being a student in public schools in the southwest region increases this chance (OR = 2,680; p = 0.04). Discussion: The reasons why socioeconomic conditions can influence a sedentary lifestyle are varied. The absence of public spaces can contribute to the increase in sedentary lifestyles in adolescents with lower socioeconomic status. Conclusion: This investigation highlights the importance of public investments in policies to encourage the practice of physical activity for adolescents, especially for females and lower socioeconomic status.How to cite this article: Carlos, Fabiangelo de Moura; Sousa, Paulo Henrique Alves de; Campos, Cezenário Gonçalves; Lamounier, Joel Alves; Bila, Wendell Costa; Romano, Márcia Christina Caetano.  Associação entre sedentarismo e nível socioeconômico em adolescentes. Revista Cuidarte. 2022;13(1): e2082. http://dx.doi.org/10.15649/cuidarte.2082
Keywords: Adolescent; Sedentary Behavior; Social Class; School Health Services